2015
DOI: 10.1038/mt.2015.157
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aggregation of Mutant Huntingtin by Nucleic Acid Aptamers In Vitro and in a Yeast Model of Huntington's Disease

Abstract: Elongated polyglutamine stretch in mutant huntingtin (mhtt) correlates well with the pathology of Huntington's disease (HD). Inhibition of aggregation of mhtt is a promising strategy to arrest disease progression. In this work, specific, high-affinity RNA aptamers were selected against monomeric mhtt (51Q-htt). Some of them inhibited its aggregation in vitro by stabilizing the monomer. They also recognized 103Q-htt but not 20Q-htt (nonpathogenic length). Inhibition of aggregation corresponded with reduced leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 53 publications
3
66
0
Order By: Relevance
“…Also, no protein was retained on the cellulose acetate membrane in this case (Figure 2d), indicating that 20Q‐htt did not form aggregates. This confirmed the specificity of thioflavin T for fibrillar aggregates 26,28 and also showed that aggregation occurred due to the expanded polyQ stretch and not due to the presence of GST tag.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Also, no protein was retained on the cellulose acetate membrane in this case (Figure 2d), indicating that 20Q‐htt did not form aggregates. This confirmed the specificity of thioflavin T for fibrillar aggregates 26,28 and also showed that aggregation occurred due to the expanded polyQ stretch and not due to the presence of GST tag.…”
Section: Resultssupporting
confidence: 74%
“…Expression and purification of GST‐20Q‐htt and GST‐51Q‐htt was carried out as described earlier 25,26 …”
Section: Methodsmentioning
confidence: 99%
“…The use of nucleic acid aptamers is one such approach that has shown preliminary promise as a therapeutic strategy. 34 Aptamers are relatively short single-stranded oligonucleotides (DNA or RNA) that assume specific, stable conformations and bind tightly and specifically to protein targets by shape complementarity. 35 , 36 , 37 They can act as a stabilizer of the target protein in two ways: (1) by sterically hindering the unfolding of target protein monomer and (2) by inhibiting protein-protein interaction via electrostatic repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a peak at lower particle size (28.61 nm) was also observed, indicating the presence of oligomers. It has been reported that shorter polyQ stretches of benign length do not aggregate at all or do so at much longer time scales than the ones used here . Thus, it may be inferred that in the presence of FLAG‐N17‐25Q‐EGFP, luciferase forms low molecular weight oligomers and the aggregation of luciferase is suppressed.…”
Section: Resultsmentioning
confidence: 62%